Digital modelling of failure of road barrier elements under impact of vehicle collision - I. V. Demiyanushko; O. V. Titov; P. S. Mikheev; I. A. Karpov (Vestnik MGSU)
Introduction. One of the effective ways of reducing the severity of consequences of road traffic accidents is the use of road barriers. The ability to withstand failure and maintain functionality across various collision scenarios determines the reliability of a barrier. An analysis of existing methods for modelling collision processes showed that the ultimate state of the structures of the impact site during a vehicle impact is usually considered to be the achievement of some ultimate value of the mechanical characteristics of the impact site material. Modelling the failure of road barrier elements, as well as the assessment of their operation after the material reaches its limiting characteristics at the moment of deformation localization, are associated with the need to take into account the failure in material models, which is necessary for an objective assessment of the operation road barrier structures, both during design and during certification analysis.Materials and methods. Barrier and frontal guardrails were selected as the object of the study. To achieve high accuracy in the results, an approach with validation based on the material – component – product scheme was applied. To construct the true stress-strain curve beyond the strength limit was used the phenomenological hardening law of Hockett and Sherby. Damage assessment was carried out using the effective plastic strain criterion, along with the GISSMO damage accumulation model. The identification of material and damage model parameters was performed using the inverse modelling method.Results. The main parameters of the material models and the GISSMO damage accumulation model were determined, and validated models of the main elements of the studied barriers were developed. Full-scale virtual crash-tests of the studied barriers were carried out using the developed validated elements, which showed good convergence with the full-scale experiment.Conclusions. As a result of the research, it was revealed that the approach using the GISSMO damage accumulation model has the greatest accuracy in describing the failure of structural elements of road barriers. To develop validated models of barriers, it is advisable to use the inverse method and validate individual elements through bench tests.